Do professional forecasters believe in uncovered interest rate parity? - Constantin Bürgi; Mengdi Song (University College Dublin, UCD School of Economics, 2023)
No, not according to our data. Using a unique data set, we run panel regressions to test whether professional forecasters believe in uncovered interest rate parity (UIP). Specifically, we test whether the interest rate expectations for individual forecasters are in line with their exchange rate expectations using the UIP condition. This new approach allows us to test directly whether forecasters believe in UIP. We find that professional forecasters generally do not believe in UIP across a range of currencies and horizons. Given the prevalence of the UIP condition in our international macro models, these results reiterate the importance of finding the drivers for these deviations.
Keywords: F31; F37; 330; Focus Economics; Bloomberg Survey; Exchange Rates